Interest Rate Repression Around the World - Calice, Pietro (World Bank, Washington, DC, 2020)
Financial repression resurfaced in the wake of the global financial crisis and may become a common feature in the post Coronavirus 2019 (COVID-19) world. To advance knowledge and inform policy advice, this paper presents a new database on interest rate controls, a popular form of financial repression, based on a survey with 108 countries representing 88 percent of global gross domestic product (GDP). The data cover such aspects of interest rate controls as types of controls, legal basis, intended objectives, methodologies, and enforcement rules. In an attempt to provide a meaningful characterization of the data, this paper also provides a preliminarily estimate of the degree of bindingness of the interest rate control regime in a country and presents simple correlations with other financial repression policies. The paper finally discusses general principles of an interest rate management policy that can minimize adverse side effects of binding controls while laying down the basis for a smooth transition or return to market determined interest rates.